All-Optical OFDM Generation for IEEE802.11a Based on Soliton Carriers Using Microring Resonators - Alavi, S. E.; Amiri, I. S.; Idrus, S. M.; Supa'at, A. S.M.; Ali, J.; Yupapin, P. P. (My University, 2014)
The optical carrier generation is the basic building block to implement all-optical orthogonal frequency-division multiplexing (OFDM) transmission. One method to optically generate single and multicarriers is to use the microring resonator (MRR). The MRRs can be used as filter devices, where generation of high-frequency (GHz) soliton signals as single and multicarriers can be performed using suitable system parameters. Here, the optical soliton in a nonlinear fiber MRR system is analyzed, using a modified add/drop system known as a Panda ring resonator connected to an add/drop system. In order to set up a transmission system, i.e., IEEE802.11a, first, 64 uniform optical carriers were generated and separated by a splitter and modulated; afterward, the spectra of the modulated optical subcarriers are overlapped, which results one optical OFDM channel band. The quadrature amplitude modulation (QAM) and 16-QAM are used for modulating the subcarriers. The generated OFDM signal is multiplexed with a single-carrier soliton and transmitted through the single-mode fiber (SMF). After photodetection, the radio frequency (RF) signal was propagated. On the receiver side, the RF signal was optically modulated and processed. The results show the generation of 64 multicarriers evenly spaced in the range from 54.09 to 55.01 GHz, where demodulation of these signals is performed, and the performance of the system is analyzed.
Keywords: IEEE802.11a; OFDM; Panda ring resonator; soliton carriers